The role of the information system on decision-making case: SONATRACH-LQS activity - BOUTIBA, Mokhtaria; DAOUD, Fatiha (Art Law and Accounting Reporter, 2025)
In today’s competitive environment, information systems (IS) are increasingly recognized as strategic assets that enhance decision-making, efficiency, and organizational performance. This study examines the contribution of IS to decision-making within SONATRACH-LQS, focusing on the relationship between system quality, information quality, service quality, and decision outcomes. A quantitative approach was adopted, with 86 valid responses collected from purposively sampled employees engaged with IS. Data analysis, conducted through SPSS and SmartPLS, revealed that IS integration improves workflow, communication, and data accessibility, thereby fostering transparency and collaboration. The results confirm that system, information, and service quality enhance both system use and user satisfaction, contributing to stronger organizational performance, despite occasional usability challenges. The study underscores IS as enablers of competitiveness and strategic monitoring, recommending continuous training, system modernization, data centralization, user-friendly design, and enhanced security.
Keywords: Information Systems (IS); Decision-Making; SONATRACH-LQS; System Quality; Organizational Performance